About the elliptic system of the differential partial equations with singular line and point on a plane - Zhusupova, D. S.; Tungatarov, A. B. (Journal of Mathematics, Mechanics and Computer Science, 2019)
In work the variety of continuous decisions of the second order elliptic system of the differential partial equations with singular line and point on a plane is received and the Robin’s problem in infinitely angular area solution is solved.